Previous tuberculosis disease as a risk factor for chronic obstructive pulmonary disease: a cross-sectional analysis of multicountry, population-based studies. Issue 11 (1st December 2021) - Kamenar, Katarina; Hossen, Shakir; Gupte, Akshay N; Siddharthan, Trishul; Pollard, Suzanne; Chowdhury, Muhammad; Rubinstein, Adolfo L; Irazola, Vilma E; Gutierrez, Laura; Miranda, J Jaime; Bernabe-Ortiz, Antonio; Alam, Dewan; et al.
Abstract : Background: Risk factors for COPD in high-income settings are well understood; however, less attention has been paid to contributors of COPD in low-income and middle-income countries (LMICs) such as pulmonary tuberculosis. We sought to study the association between previous tuberculosis disease and COPD by using pooled population-based cross-sectional data in 13 geographically diverse, low-resource settings. Methods: We pooled six cohorts in 13 different LMIC settings, 6 countries and 3 continents to study the relationship between self-reported previous tuberculosis disease and lung function outcomes including COPD (defined as a postbronchodilator forced expiratory volume in one second (FEV1 )/forced vital capacity (FVC) below the lower limit of normal). Multivariable regressions with random effects were used to examine the association between previous tuberculosis disease and lung function outcomes. Results: We analysed data for 12 396 participants (median age 54.0 years, 51.5% male); 332 (2.7%) of the participants had previous tuberculosis disease. Overall prevalence of COPD was 8.8% (range 1.7%–15.5% across sites). COPD was four times more common among those with previous tuberculosis disease (25.7% vs 8.3% without previous tuberculosis disease, p<0.001). The adjusted odds of having COPD was 3.78 times higher (95% CI 2.87 to 4.98) for participants with previous tuberculosis disease than those without a history of tuberculosis disease. The attributable fraction of COPD due to previous tuberculosis disease in the study sample was 6.9% (95% CI 4.8% to 9.6%). Participants with previous tuberculosis disease also had lower prebronchodilator Z-scores for FEV1 (−0.70, 95% CI −0.84 to −0.55), FVC (−0.44, 95% CI −0.59 to −0.29) and the FEV1 :FVC ratio (−0.63, 95% CI −0.76 to −0.51) when compared with those without previous tuberculosis disease. Conclusions: Previous tuberculosis disease is a significant and under-recognised risk factor for COPD and poor lung function in LMICs. Better tuberculosis control will also likely reduce the global burden of COPD.